2012
DOI: 10.1002/app.38797
|View full text |Cite
|
Sign up to set email alerts
|

Study on poly(D,L‐lactic) microspheres embedded in calcium alginate hydrogel beads as dual drug delivery systems

Abstract: This work is to develop a novel dual drug delivery system that can simultaneously load and release 18β‐glycyrrhetinic acid (GA, a hydrophobic drug) and bovine serum albumin (BSA, hydrophilic model drug) in a single formulation. The system consists of poly(D,L‐lactic) (PDLLA) microspheres embedded in calcium alginate hydrogel beads. The GA‐loaded microspheres were first prepared and then dispersed in the aqueous solution of sodium alginate and BSA. The resulting suspension was dropped into aqueous calcium chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…These poor EE data arise from the fact that considerable amounts of progesterone are not encapsulated but dispersed as free drug crystals in the aqueous continuous phase. Using methylene chloride for solvent evaporation to encapsulate piroxicam and glycyrrhetinic acid into PLGA microspheres also led to poor EE values ranging from 15.1 to 33.6% . These data are in accordance with our results demonstrating that the preparation of microspheres through solvent evaporation has a tendency to show a poor EE value due to drug crystallization in a continuous phase.…”
Section: Resultssupporting
confidence: 91%
“…These poor EE data arise from the fact that considerable amounts of progesterone are not encapsulated but dispersed as free drug crystals in the aqueous continuous phase. Using methylene chloride for solvent evaporation to encapsulate piroxicam and glycyrrhetinic acid into PLGA microspheres also led to poor EE values ranging from 15.1 to 33.6% . These data are in accordance with our results demonstrating that the preparation of microspheres through solvent evaporation has a tendency to show a poor EE value due to drug crystallization in a continuous phase.…”
Section: Resultssupporting
confidence: 91%
“…Hydrogels are 3-dimensionally interconnected hydrophilic polymers, which can absorb an extensive amount of water within the structures without being dissolved in water. Since the chemical, electrical, and mechanical properties of polymer hydrogels could be quite analogous with those present in biological tissues, there have been extensive efforts to utilize the hydrogels in biological applications such as drug delivery (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), wound/burn dressing (13,14), scaffolds for tissue engineering (15)(16)(17), and others (18)(19)(20)(21). In particular, the inclusion of drugs inside polymer hydrogels may represent an innovative drug delivery system because the release rate of the loaded drugs can be regulated by external stimuli (1,2,(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, the change in pH (2,3), temperature (1,7,9), and light (4) has triggered the swelling, shrinkage, or degradation of the hydrogels to release the drugs in a controlled way. Alternatively, in the absence of the external stimuli, the slow diffusion nature of the drug release can ensure a constant delivery as well as prolonged duration of drugs, which is necessary for exerting long-term efficacy (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The degradation diversity between the two types of microspheres were ascribed to their different interior structures. According to the reports, microspheres prepared by DEEM exhibited a capsule or honeycomb interior structure, and microspheres prepared by SEEM were solid spheres. Through the ultrasonic pulverization of microspheres, we confirmed that the microspheres prepared by DEEM in this study possessed a honeycomb interior structure [Figure (B)], but the microspheres prepared by SEEM was difficult to break; this, in turn, suggested that it was a solid sphere as reported.…”
Section: Resultsmentioning
confidence: 99%